2018
DOI: 10.1002/eco.1933
|View full text |Cite
|
Sign up to set email alerts
|

Remote‐sensing‐derived fractures and shrub patterns to identify groundwater dependence

Abstract: The identification and location of groundwater‐dependent ecosystems are the first steps in protecting and managing them. Such identifications are challenging where the surface expressions of groundwater are not obvious. This work presents a remote‐sensing‐based approach to infer the groundwater dependence of semiarid shrubs from their association with fractures that facilitate root access to groundwater. As a case study, we used the Ziziphus lotus matorral in south‐east Spain, a priority conservation habitat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
(89 reference statements)
0
18
0
2
Order By: Relevance
“…During recent decades, several studies reported that Ziziphus lotus is declining in SE Spain, Sicily and Cyprus ( [49]). In Europe, the largest population occurs in the Cabo de Gata-Níjar Natural Park (SE Spain), where an increased mortality of individual shrubs of all ages was observed in the last decade ( [50,51]). …”
Section: Study Areas and Datasets Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…During recent decades, several studies reported that Ziziphus lotus is declining in SE Spain, Sicily and Cyprus ( [49]). In Europe, the largest population occurs in the Cabo de Gata-Níjar Natural Park (SE Spain), where an increased mortality of individual shrubs of all ages was observed in the last decade ( [50,51]). …”
Section: Study Areas and Datasets Constructionmentioning
confidence: 99%
“…However, in test-zone-2 some trees do coexist, whose presence may affect the detection accuracies. In those cases, the learning of the CNN-model can be improved by using more spectral bands or temporal information, e.g., including Near Infrared, Digital Surface Model (DSM) or the seasonal NDVI dynamics [51,58].…”
Section: Cnn-detector Versus Obia-detectormentioning
confidence: 99%
“…Ziziphus lotus (L.) Lam, a long-lived shrub from Mediterranean drylands [27], shows characteristics for a multi-temporal analysis of the spatial distribution in its populations with OBIA. This shrub species depends on groundwater [28], forms fertility islands, and is considered an engineering species [29] of an ecosystem of interest for conservation at the European level (Directive 92/43/CEE). The main European population of the shrub species is located in a flat coastal area surrounded by greenhouses in the Cabo de Gata-Níjar Natural Park, Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1944, several studies have evaluated this community of Z. lotus. Shrub patterns to identify groundwater dependence [28], the formations of shrubs in dunes [37], shrub spatial aggregation and consequences for reproductive success [29], and mutual positive effects between shrubs [38] have been researched. Yet, the monitoring of the shrub population dynamics has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although an emerging body of literature in the last decades has focused on researching dryland ecosystems, there is a surprisingly weak understanding of biohydrological processes. One of the processes is groundwater access by vegetation, which Guirado et al () studied using a non‐destructive low‐cost remote‐sensing‐based approach. This approach combined object‐based image analysis of high‐resolution orthoimages to map shrub individuals with geomorphometric analysis of a lidar‐derived terrain model to map fractures that roots use to access groundwater.…”
mentioning
confidence: 99%